ANALISIS SENSITIVITAS DAN PREDIKSI PERFORMA PRODUKSI PADA OPERASI ACID FRACTURING DI RESERVOIR KARBONAT - Malyan Ibrahim, Terihamka
Acid fracturing is one of well stimulation method which occasionally used in carbonate reservoir. Due it’s complexity, acid fracturing should be designed carefully. Some design parameters affecting the acid fracturing such as the acid, acid concentration, fracture thickness, injection rate, and injection duration. The success of an acid fracturing operation often is observed from skin parameter, which negative value of skin indicates the existence of stimulation in reservoir. Another parameter we can observe is conductivity. This paper will serve sensitivity analysis of skin and conductivity to specified design parameter. A prediction of production performance after acid fractured also presented in this paper. Besides that, it will present production performance of a reservoir without acid fracturing. Later, we will see comparison of production performance with and without acid fracturing.